Pengaruh Pendapatan Asli Daerah, Belanja Modal dan Dana Bagi Hasil Migas terhadap Pertumbuhan Ekonomi di Aceh - Fatmawati; Ulya, Zikriatul; Hamid, Abdul (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
Economic growth is an indicator of the success of development implementation which can be used as a macro benchmark and changes in Gross Regional Domestic Product (GRDP) in a region. GRDP is the amount of added value produced by all business units in a region. The higher the economic growth of an area indicates the better the economic activity in that area. This research aims to determine the influence of PAD, Capital Expenditures, Oil and Gas Profit Sharing Funds on economic growth in Aceh, with the selected year starting from 2011-2020. This research uses quantitative methods and the data used is secondary data in the form of the Aceh Government Financial Report and the General Ministry of Finance. The data analysis method uses multiple linear regression analysis. The results of the research show that local revenue has a positive and significant effect on economic growth in Aceh with a significance value of 0.009 < 0.05 and a value of tcount of 3.778 > ttable l value of 1.8945. Capital expenditure has no significant effect on economic growth in Aceh with a significance value of 0.464 > 0.05 and a t value of -0.783 < t table value of 1.8945. Oil and gas profit sharing has no significant effect on economic growth in Aceh with a significance value of 0.521 > 0.05 and a tcount value of -0.682 < ttable value of 1.8945. The results of the F test (simultaneous) show that the significance value of F is 0.001 < 0.05 and the F value is 24.832 > 19.35 indicating that there is a positive and significant influence of PAD, Capital Expenditures, Oil and Gas Profit Sharing on economic growth in Aceh.